Targeted brain delivery of RVG29‐modified rifampicin‐loaded nanoparticles for Alzheimer's disease treatment and diagnosis - Ruiyi Zhou; Lihong Zhu; Zhaohao Zeng; Rixin Luo; Jiawei Zhang; Rui Guo; Lei Zhang; Qunying Zhang; Wei Bi (Bioengineering & Translational Medicine, 2022)
Abstract Alzheimer's disease (AD) is an aging‐related neurodegenerative disease. The main pathological features of AD are β‐amyloid protein (Aβ) deposition and tau protein hyperphosphorylation. Currently, there are no effective drugs for the etiological treatment of AD. Rifampicin (RIF) is a semi‐synthetic broad‐spectrum antibiotic with anti‐β‐amyloid deposition, anti‐inflammatory, anti‐apoptosis, and neuroprotective effects, but its application in AD treatment has been limited for its strong hydrophobicity, high toxicity, short half‐life, low bioavailability, and blood–brain barrier hindrance. We designed a novel brain‐targeted and MRI‐characteristic nanomedicine via loading rabies virus protein 29 (RVG29), rifampicin, and Gd on poly (l‐lactide) nanoparticles (RIF@PLA‐PEG‐Gd/Mal‐RVG29). The cytotoxicity assay demonstrated that RIF@PLA‐PEG‐Gd/Mal‐RVG29 had favorable biocompatibility and security. Fluorescence imaging in vivo showed that PLA‐PEG‐Gd/Mal‐RVG29 could deliver rifampicin into the brain by enhancing cellular uptake and brain targeting performance, leading to improvement of the bioavailability of rifampicin. In in vivo study, RIF@PLA‐PEG‐Gd/Mal‐RVG29 improved the spatial learning and memory capability of APP/PS1 mice in the Morris water maze, as compared to rifampicin. Immunofluorescence, TEM, immunoblotting, and H&E staining revealed that RIF@PLA‐PEG‐Gd/Mal‐RVG29 reduced Aβ deposition in hippocampal and cortex of APP/PS1 mice, improved the damage of synaptic ultrastructure, increased the expression level of PSD95 and SYP, as well as reduced the necrosis of neurons. These findings suggest that RIF@PLA‐PEG‐Gd/Mal‐RVG29 may be an effective strategy for the treatment of AD.